1H‐decoupling and Isotopic Labeling for the Measurement of the Longitudinal Relaxation Time of Hyperpolarized 13C‐Methylenes in Choline Analogs. Issue 11 (24th April 2019) - Uppala, Sivaranjan; Gamliel, Ayelet; Harris, Talia; Sosna, Jacob; Gomori, J. Moshe; Jerschow, Alexej; Katz‐Brull, Rachel
Abstract: The T1 of a hyperpolarized site in solution is a key parameter that determines the time‐window in which its NMR signals are observable. For 13 C sites adjacent to protons, 1 H‐decoupling has been shown to increase the hyperpolarized signal resolution and SNR. Additionally, polarization transfer to protons has shown utility in increasing the sensitivity of detection. However, 1 H‐decoupling could lead to a change in the decay rate of a hyperpolarized 13 C site. Here we tested this possible effect in a case where the protons are directly bound to an sp 3 hyperpolarized 13 C site (using [1, 2‐ 13 C2 ]choline) and 1 H‐decoupling was applied continuously throughout the hyperpolarized decay measurement. We found that 1 H‐decoupling did not lead to any significant changes in the 13 C polarization decay time but did result in the expected collapse of J‐coupling and produced sharper signals. This result suggested that 1 H‐decoupling did not affect the decay rate of hyperpolarized sp 3 13 C sites. The deuterium‐substitution approach (using [1, 1, 2, 2‐D4, 1‐ 13 C]choline) showed a dramatic prolongation of T1 . Upper bounds on the T1 of all investigated sites were calculated. Abstract :